SUN5 Interacting With Nesprin3 Plays an Essential Role in Sperm Head-to-Tail Linkage: Research on Sun5 Gene Knockout Mice - Zhang, Yunfei; Yang, Linfei; Huang, Lihua; Liu, Gang; Nie, Xinmin; Zhang, Xinxing; Xing, Xiaowei (Frontiers in Cell and Developmental Biology, 2021)
Acephalic spermatozoa syndrome is a rare genetic and reproductive disease. Recent studies have shown that approximately 33~47% of patients with acephalic spermatozoa syndrome have SUN5 mutations, but the molecular mechanism underlying this phenomenon has not been elucidated. In this study, we generated Sun5 knockout mice and found that the head-to-tail linkage was broken in Sun5-/- mice, which was similar to human acephalic spermatozoa syndrome. Furthermore, ultrastructural imaging revealed that the head-tail coupling apparatus (HTCA) and the centrosome were distant from the nucleus at steps 9-10 during spermatid elongation. With the manchette disappearing at steps 13-14, the head and the tail segregated. To explore the molecular mechanism underlying this process, bioinformatic analysis was performed and showed that Sun5 may interact with Nesprin3. Further coimmunoprecipitation (Co-IP) and immunofluorescence assays confirmed that Sun5 and Nesprin3 were indeed bona fide interaction partners that formed the linker of the nucleoskeleton and cytoskeleton (LINC) complex participating in the connection of the head and tail of spermatozoa. Nesprin3 was located posterior and anterior to the nucleus during spermiogenesis in wild-type mice, whereas it lost its localization at the implantation fossa of the posterior region in Sun5-/- mice. Without correct localization of Nesprin3 at the nuclear membrane, the centrosome, which is the originator of the flagellum, was distant from the nucleus, which led to the separation of the head and tail. In addition, iTRAQ results showed that 47 proteins were upregulated, and 56 proteins were downregulated, in the testis in Sun5-/- mice, and the downregulation of spermatogenesis-related proteins (Odf1 and Odf2) may also contribute to the damage to the spermatozoa head-to-tail linkage. Our findings suggested that Sun5 is essential for the localization of Nesprin3 at the posterior nuclear membrane, which plays an essential role in the sperm head-tail connection.